Associating Flexible Regulation of Emotional Expression With Psychopathological Symptoms - Gonzalez-Escamilla, Gabriel; Dörfel, Denise; Becke, Miriam; Trefz, Janina; Bonanno, George A.; Groppa, Sergiu (Frontiers in Behavioral Neuroscience, 2022)
Background: Stressful situations and psychopathology symptoms (e.g., depression and anxiety) shape how individuals regulate and respond to others’ emotions. However, how emotional expressions influence mental health and impact intrapersonal and interpersonal experiences is still unclear. Objective: Here, we used the Flexible Regulation of Emotional Expression (FREE) scale to explore the relationship between emotion expression abilities with affective symptoms and mental health markers. Methods: From a sample of 351 participants, we firstly validate a German version of the FREE scale on a final sample of 222 participants located in Germany, recruited through an online platform. Following, we performed confirmatory factor analyses to assess the model structure of the FREE-scale. We then utilize a LASSO regression to determine which indicators of psychopathology symptoms and mental health are related to emotional expressive regulation and determine their particular interactions through the general linear model. Results: We replicated the FREE scale’s four latent factors (i.e. ability to enhance and suppress positive as well as negative emotional expressions). After selection of relevant instruments through LASSO regression, the suppress ability showed specific negative associations with depression (r=.2) and stress symptoms (r=.16) and positive associations with readiness to confront distressing situations (r=.25), self-support (r=.2) and tolerance of emotions (r=.2). Both, emotional expression enhance and suppress abilities positively associated with coping markers (resilience) and emotion regulation skills. Finally, the interaction effects between emotional flexibility abilities and stress, depression, and anxiety symptoms evidenced that consistently with the flexibility theory, enhance and suppress abilities may predict psychopathological symptoms. Conclusions: These findings emphasize the importance of considering the flexibility to express emotions as a relevant factor for preserved mental health or development of psychopathological symptoms and indicate that online surveys may serve as a reliable indicator of mental health.